2015
DOI: 10.1007/s00590-015-1696-0
|View full text |Cite
|
Sign up to set email alerts
|

Similar effectiveness of the open versus endoscopic technique for carpal tunnel syndrome: a prospective randomized trial

Abstract: This prospective randomized study aims at evaluating the electrophysiological results of endoscopic and open carpal ligament release in patients with carpal tunnel syndrome. Included in the study were 41 patients diagnosed with carpal tunnel syndrome (21 hands in the endoscopic group and 20 hands in the open group). The Boston questionnaire was administered preoperatively and postoperatively to the patients, and their functional capacities and symptom severities were recorded. Physical examination was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…This difference is statistically significant at p < 0.05. These results are similar to those in [8–11, 20, 27–31].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This difference is statistically significant at p < 0.05. These results are similar to those in [8–11, 20, 27–31].…”
Section: Discussionsupporting
confidence: 91%
“…Kang (2013) noted that 34 (65%) out of 52 patients, who underwent bilateral decompression (with minimally invasive and endoscopic approaches), would prefer endoscopic surgery [25]. Many authors describe a low recurrence rate and faster recovery after endoscopic decompression of the median nerve [8–11]. Sayegh and Strauch described the long-term effect from open and endoscopic decompression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have investigated the outcomes of open and endoscopic carpal tunnel release 12. Sayegh et al13 published a meta-analysis of good-quality randomized controlled clinical trials comparing the two techniques and they concluded that symptom relief, severity, and functional status were similar for both techniques; however, patients who underwent endoscopic surgery had earlier return of grip and pinch strength.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, large series of nerve releases to treat median carpal tunnel syndrome (CTS) show a complication rate [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] (treatment failure) that varies from 3 to 25% and a reoperating rate of 12% [3,[7][8][9][10][11]17]. Additionally, multiple neurolysis (external or internal) alone is rarely the appropriate treatment for true recurring carpal tunnel syndrome, because the re-operated nerve is often trapped in fibrous scar tissue resulting from the repeated disintegration of the surrounding gliding tissue [1,7,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%